ANALISIS TINGKAT KESEHATAN KEUANGAN PT. ASURANSI TAKAFUL KELUARGA BERDASARKAN METODE RISK-BASED CAPITAL (RBC) DAN EARLY WARNING SYSTEM (EWS) PERIODE 2025 - Milatun Nafiah; Lely Ana Ferawati Ekaningsih (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
This study aims to analyze the financial health of PT Asuransi Takaful Keluarga for the 2025 period. The research novelty lies in integrating Risk-Based Capital (RBC) and Early Warning System (EWS) methods to comprehensively capture the solvency and operational performance of Islamic insurance. Using a descriptive-quantitative approach, secondary data from audited 2025 financial statements were analyzed based on OJK Regulation No. 71/POJK.05/2016. The findings indicate a highly healthy financial condition; RBC ratios for both Tabarru' and Corporate Funds are well above the regulatory minimum, supported by liquid and productive EWS indicators. However, over-capitalization is identified in the Corporate Fund due to conservative governance, and the Tabarru' Fund claim ratio approaches the ideal threshold. This study implies that the industry should optimize capital allocation and mitigate underwriting deficits, while providing regulators a reference to refine risk-based supervisory parameters in Islamic insurance.